Lion Sport Technology [LST] Sdn Bhd / Amir Hamzah Nazarali - Nazarali, Amir Hamzah; Mohd Khairi, Harris; Rosman, Muhamad Danish Aiman; Ishak, Muhammad Adib; Rosli, Muhammad Akmal (2022)
Throughout this entire technological era, a device plays a vital role for human living in this world. The following detailing about new product development (NPD), it does act as process of innovating product into the market. We assure the product engage with customer preferences, and increase competition with others company. We managed to get a lot of preferences and develop a product that meet people needs especially among athletes and coaches. Thus improve our knowledge to our 2 in 1 product in the real world of sports. We managed to get the chance to performing research and development and implemented it through questionnaire. Thus, complete our product analysis. Finally, further discussion has been documented below proceed with more detailing, precise and focus on NPD. It will involve about introduction to our company and detailing on NPD involving product prototype. In short, development of new product is Compression Sport Device involve 2 in 1 product. An idea generation based on Johor Darul Ta’zim Football Club that are well known with their technology and facilities they delivered for their players. The design level and features of the product are specified to performance analysis, durability, and its own electronic technology. In conclusion, feedbacks from athletes, exercise practitioners and coaches are helpful and meet the demands and nowadays trends.